Pengaruh Manajemen Waktu dan Dukungan Teman Sebaya Terhadap Motivasi Penyelesaian Tugas Akhir Mahasiswa - Komang Putri Yurika Ardani; I Putu Arya Dharmayasa (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This study aims to analyze the influence of time management and peer support on the motivation to complete final assignments among students of the Faculty of Economics, Universitas Pendidikan Ganesha. The research employed a quantitative approach with a causal design. The population of this study consisted of students from the Faculty of Economics, with a total sample of 104 participants. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 25. The results indicate that: (1) time management has a positive and significant effect on the motivation to complete final assignments; (2) peer support has a positive and significant effect on the motivation to complete final assignments; and (3) simultaneously, time management and peer support have a positive and significant effect on students’ motivation to complete their final assignments. The findings of this study are expected to serve as a reference for both students and academic stakeholders in improving effective and efficient strategies for completing their studies.